BRAF and MEK inhibitors rechallenge as effective treatment for patients with metastatic melanoma. Issue 5 (October 2020) - Cybulska-Stopa, Bożena; Rogala, Paweł; Czarnecka, Anna M.; Galus, Łukasz; Dziura, Robert; Rajczykowski, Marcin; Kubiatowski, Tomasz; Wiśniewska, Magdalena; Gęga-Czarnota, Adrianna; Teterycz, Paweł; Ziobro, Marek; Suwiński, Rafał; et al.
Abstract : Despite considerable progress made in the treatment of patients with advanced melanoma, the majority of the patients treated with BRAF and mitogen-activated protein inhibitors (BRAFi and MEKi) experience a disease progression due to acquired resistance. Currently, ongoing studies explore the possibility to overcome or reverse this process. Our multicenter retrospective analysis included 51 patients with metastatic BRAF -mutated melanoma who had previously progressed on BRAFi/MEKi than had progressed on immunotherapy (anti-progression disease-1 or anti-cytotoxic T-lymphocyte-associated protein 4) and next were rechallenged with BRAFi/MEKi. Median age at BRAFi/MEKi rechallenge was 56 (range: 31–82 y/o). Median overall survival from the start of the first BRAFi/MEKi therapy and from rechallenge BRAFi/MEKi treatment was 29.7 and 9.3 months, respectively, whereas median progression-free survival was 10.5 and 5.9 months, respectively. Six-month, annual, and 2-year overall survival rates on both treatments were: 98% and 55%, 92% and 29%, and 69% and 2%, respectively. A response rate to treatment was higher in the group receiving BRAFi/MEKi for the first time as compared with the group receiving BRAFi/MEKi rechallenge and was overall response rate 72% and 27%; disease control rate 92% and 63%. Time interval between the end of the first BRAFi/MEKi treatment and the beginning of BRAFi/MEKi rechallenge did not influence median overall survival or progression-free survival. A lower toxicity rate was noted with BRAFi/MEKi rechallenge. BRAFi/MEKi rechallenge treatment remains clinically important and is associated with the lower toxicity. BRAFi/MEKi rechallenge efficacy is higher in patients who are in good performance status, with normal lactate dehydrogenase, and without brain metastases. Abstract : Supplemental Digital Content is available in the text.